Radiographers’ knowledge, attitude and adherence to standard COVID-19 precautions and the policy implications: a national cross-sectional study in Nigeria - Charles Ikechukwu Ezema; Okechukwu Felix Erondu; Ogochukwu Kelechi Onyeso; Chiedozie James Alumona; Andrew Wueseter Ijever; Charity Ndidiamaka Amarachukwu; Amaeze Augustine Amaeze (Annals of Medicine, 2023)
AbstractBackground We investigated the knowledge of COVID-19 pathogenesis and prevention, attitude, and adherence to safe clinical practices among radiographers during the pandemic and made some informed policy recommendations.Materials and methods The study was an online cross-sectional survey. The questionnaire captured data on respondents’ demographics, knowledge of COVID-19, attitudes, practices, and standard precaution adherence during the pandemic. Data were analysed using descriptive statistics, Pearson’s correlation and one-way ANOVA tests.Results Of the 255 respondents, 17.3% were actively involved in the management of COVID-19 cases. Participants had high scores regarding their knowledge of COVID-19 pathology (82.46 ± 8.67%), prevention (93.43 ± 7.11%) and attitude (74.11 ± 11.61%), but low compliance to safety precautions (56.08 ± 18.56%). Knowledge about COVID-19 prevention strategies differed significantly across educational qualifications, F(3, 251) = 4.62, p = .004. Similarly, levels of compliance with safety precautions differed across educational qualification (F[3, 251] = 4.53, p = .004) and years-in-practice (F[4, 250] = 4.17, p = .003).Conclusion Participants’ adherence to standard COVID-19 precautions was low. The level of professional qualification influenced participants’ knowledge and safe practices during the pandemic. Upgrading the aseptic techniques and amenities in practice settings and broadening the infectious diseases modules in the entry-level and continuous professional education may improve radiographers’ response to COVID-19 and future pandemics.Key messagesRadiographers whose qualifications were lower than a bachelor’s degree had significantly less knowledge of COVID-19 prevention.Generally, radiographers had a positive attitude towards safe practices during the pandemic, but inadequate education, standard operational guidelines and resources affected their level of adherence.Apart from the shortage of personal protective equipment, poor infrastructural design and inadequate hygienic facilities such as handwashing stations, running water and non-contact hand sanitizer dispensers hampered adherence to COVID-19 precautions in low-resource settings.